2003
DOI: 10.1111/j.1151-2916.2003.tb03340.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Theory of Diffusion in Alumina

Abstract: Despite all the work conducted over many decades, there remains a major problem in understanding diffusion in alumina. It is certain that all measurements of diffusion in alumina refer to extrinsic diffusion. However, the experimental activation energy is larger than any theoretical prediction by a factor of 2. The problem with grain boundary diffusion is, if anything, worse. The most complete set of experimental data suggests that the activation energy for boundary diffusion is 50% larger than for bulk diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 31 publications
8
67
2
Order By: Relevance
“…This data shows that the low-energy jumps, previously predicted and simulated, do not contribute to the macroscopic diffusion coefficient as they only allow migration of the vacancy within the small triangles. This non-continuity was one of the hypotheses put forward by Harding et al [31], and is now confirmed by the present results and may explain the discrepancy between simulation and experimental migration energies pointed out by Heuer [2]. The next lowest energy class is the third one, which due to its interconnected nature is expected to be the diffusion-dominating class.…”
Section: Metadynamics Calculationssupporting
confidence: 78%
“…This data shows that the low-energy jumps, previously predicted and simulated, do not contribute to the macroscopic diffusion coefficient as they only allow migration of the vacancy within the small triangles. This non-continuity was one of the hypotheses put forward by Harding et al [31], and is now confirmed by the present results and may explain the discrepancy between simulation and experimental migration energies pointed out by Heuer [2]. The next lowest energy class is the third one, which due to its interconnected nature is expected to be the diffusion-dominating class.…”
Section: Metadynamics Calculationssupporting
confidence: 78%
“…However, it was found that the diffusivity of oxygen in alumina was not quite sensitive to the amount of point defects as expected. 3,21,48 Neither varying the partial pressure of O 2 gas 49 nor doping alumina with aliovalent solutes 48 would induce significant changes to the oxygen diffusivity in α-Al 2 O 3 specimens. To explain these experimental data, many diffusion mechanisms, such as, vacancyatom exchange mechanism, 3 interstitial mechanism 21,50 , point defect cluster mechanism 49 , AlO divacancy mechanism 4 , and hydroxyl/peroxide mechanism.…”
Section: Further Notesmentioning
confidence: 99%
“…3,8,9 Some impurities such as Si 51 , Mg 51 , Ca 52 , Y 13 prefer segregating themself onto the grain boundaries from the bulk alumina. As a result, even if the concentrations of the impurities are low in the whole sample, the GB regions of the sample could have quite high concentration of the 22 impurities.…”
Section: Further Notesmentioning
confidence: 99%
“…28 Because oxide grain boundaries have been shown experimentally to have an ionic conductivity many orders of magnitude higher than oxide grains, 29 it was considered that grain boundaries in the passive film are less resistive to ion transfer, and thus the potential drop within the oxide barrier layer at the metal/oxide/electrolyte interface is locally smaller at grain boundaries. As a direct consequence, the potential drops at the metal/oxide or/and at the oxide/electrolyte interfaces are locally larger and thus favor the interfacial reaction leading to passivity breakdown at these intergranular boundaries of the passive film.…”
mentioning
confidence: 99%